2014
DOI: 10.3390/molecules190812336
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of an Enzymatic Extract from Bentong Ginger (Zingiber officinale var. Bentong)

Abstract: Extraction of protease from a local ginger rhizome (Zingiber officinale var. Bentong) was carried out. The effect of extraction pH (6.4, 6.8, 7.0, 7.2, 7.6, 8.0, 8.4, and 8.8) and stabilizers (0.2% ascorbic acid, 0.2% ascorbic acid and 5 mM EDTA, or 10 mM cysteine and 5 mM EDTA) on protease activity during extraction was examined. pH 7.0 potassium phosphate buffer and 10 mM cysteine in combination with 5 mM EDTA as stabilizer were found to be the most effective conditions. The extraction procedure yielded 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…Similarly, various studies on different plant proteases, have also reported similar findings (Huang et al, 2011;Nafi et al, 2014).…”
Section: Ta B L E 1 Overall Tpp Purification Profile Of Crown Bromela...supporting
confidence: 61%
“…Similarly, various studies on different plant proteases, have also reported similar findings (Huang et al, 2011;Nafi et al, 2014).…”
Section: Ta B L E 1 Overall Tpp Purification Profile Of Crown Bromela...supporting
confidence: 61%
“…It has bigger rhizomes with lower fibrous pulp compared to other Malaysian cultivars of ginger [1]. Due to the unique characteristics of Bentong ginger, there is a high demand for its rhizomes in the domestic and international markets [2]. Since the rhizomes are eco-nomically utilized parts of the plant, using a high proportion of ginger rhizomes as planting materials for cultivating the plant in the next growing season negatively affects its supply in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 illustrates that bromelain shows substantial proteolytic activity capable of cleaving peptide bonds at the arginine, phenylalanine, and tyro-sine regions, at pH 6.5-8 with a temperatures between 55 • C and 60 • C (Arshad et al, 2014). Meanwhile, the zingibain enzyme from ginger rhizome displayed the maximum proteolytic activity at 60 • C and pH 6-8, cleaving the peptide linkage at the proline region (Choi & Laursen, 2000;Nafi et al, 2014). Histidine-159, which is involved in general acid/base catalysis, is one of the catalytically significant residues in zingibain (Choi & Laursen, 2000).…”
Section: Enzyme-aided Treatmentmentioning
confidence: 99%